The Poetry of Li He - Ashmore, Robert (Library of Chinese Humanities, 2023)
Li He (790-816) gained his early renown particularly for his lyrical reimaginings of lost song traditions from ancient times. The poet's premature death, along with the otherworldly quality of many of his works, led later readers to view Li He as the emblematic cursed poet, whose lyrical fascination with ancient history, with ghosts, and with celestial and demonic beings seemed to have presaged the brevity of poet's own earthly existence.